Correlates of patterns of cannabis use, abuse and dependence: evidence from two national surveys in Ireland. (24th February 2021) - Millar, Seán R; Mongan, Deirdre; O'Dwyer, Claire; Long, Jean; Smyth, Bobby P; Perry, Ivan J; Galvin, Brian
Abstract: Background: Knowledge of factors relating to patterns of cannabis use is important for informing drug policy. This study determined factors associated with recent and current cannabis use. In addition, we explored factors related to having a cannabis use disorder (CUD)—defined using the Diagnostic and Statistical Manual of Psychiatric Disorders—among current users. Methods: We analyzed data from Ireland's 2010–11 and 2014–15 National Drug Prevalence Surveys, which recruited 5134 and 7005 individuals respectively, aged 15 years or more, living in private households. Multinomial logistic regression was used to identify factors associated with recent (last year) and current (last month) cannabis use compared to experiential use. Binary logistic regression was used to determine factors related to CUD among current users. Results: The weighted prevalence of experiential cannabis use was 18.3%, with 3.0% and 3.3% of participants indicating recent or current use, respectively; 41.3% of current users indicated having a CUD. Factors associated with both recent or current cannabis use included younger age, not being married or cohabiting, having no dependent children and current use of tobacco or alcohol. Male gender, younger age and lower educational levels were significantly related to CUD among current users. Conclusions: Males, adolescents/young adults and individuals with lower educational levels are more likely to be current users of cannabis and are at a greater risk of having a CUD. Health professionals should be aware of these factors to improve detection and prevention of CUD.